Increased Clot Formation in the Absence of Increased Thrombin Generation in Patients with Peripheral Arterial Disease: A Case–Control Study - Kleinegris, Marie-Claire F.; Konings, Joke; Daemen, Jan W.; Henskens, Yvonne; de Laat, Bas; Spronk, Henri M. H.; ten Cate-Hoek, Arina J.; ten Cate, Hugo (Frontiers in Cardiovascular Medicine, 2017)
Increased clot formation in the absence of increased thrombin generation in patients with peripheral arterial disease; a case-control study.